An empirical taxonomy of sports - Prot, Franjo (Array, 2002)
The sample of 2280 female students of different subjects of Faculty of philosophy were given sport preferences questionnaire containing the list of 62 sports and recreational activities to be evaluated on five-point scale. Taxonomy of sport preferences was established by component analysis of similarity matrix with orthoblique transformation of principle axes. Eleven factors were extracted, defined as: water sports factor (1), strenght developing sports factor (2), popular ball and racket sports factor (3), classical sports factor (4), combat sports factor (5), factor of sports mostly taking place in natural environment (6), factor of sports using arms (7), single factor defined by aerobics (8), skating and skiing factor (9), "extreme" sports factor (10), and factor of less known and less popular sports (11).